Effect of Temperature on Life Cycle Traits of Callosobruchus spp. Infesting Stored Mungbeans - Saurabh Singh; Rakesh Pandey; Ashutosh Rai; Mukesh Kumar Mishra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Bruchid beetles are primary pests of stored pulses, causing significant post-harvest losses. Callosobruchus maculatus (F.) and Callosobruchus chinensis L. are the most common species in tropical and subtropical regions, often co-occurring in storage. This study aimed to evaluate the temperature-dependent life cycle parameters of C. maculatus and C. chinensis infesting mungbean (Vigna radiata L.) seeds. The life cycle of both species was observed under two different conditions: controlled (27 ± 1°C, 65 ± 5% RH) and room temperature: uncontrolled (34 ± 4°C, 70 ± 5% RH). Three experimental sets were maintained, each with 10 replicates in completely randomized design. Life cycle duration was recorded, and data were analyzed using descriptive statistics to determine mean durations. Under controlled conditions, C. maculatus and C. chinensis completed their life cycles in 33.40–39.80 days (mean 36.84 ± 1.61) and 31.30–36.70 days (mean 34.20 ± 1.23), respectively. At room temperature, development accelerated, with durations of 28.53–32.70 days (mean 30.84 ± 1.17) and 26.30–31.80 days (mean 29.32 ± 1.55), respectively. Higher temperatures shorten the life cycle of both beetle species, potentially increasing infestation rates. These findings highlight the need for temperature management and timely monitoring in stored mungbean to reduce bruchid damage and improve storage outcomes.